2013
DOI: 10.1093/bja/aet070
|View full text |Cite
|
Sign up to set email alerts
|

Complications of non-invasive ventilation techniques: a comprehensive qualitative review of randomized trials

Abstract: Non-invasive ventilation (NIV) has become a common treatment for acute and chronic respiratory failure. In comparison with conventional invasive mechanical ventilation, NIV has the advantages of reducing patient discomfort, procedural complications, and mortality. However, NIV is associated with frequent uncomfortable or even life-threatening adverse effects, and patients should be thoroughly screened beforehand to reduce potential severe complications. We performed a detailed review of the relevant medical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(201 citation statements)
references
References 139 publications
2
183
0
16
Order By: Relevance
“…They concluded that, careful patient selection and taking into account the risk factors and contraindications are important for NIV to be successful and safe. 1 Contraindications for NIV include respiratory or cardiac arrest, hypotension or shock, poor airway protective reflexes, recent upper airway surgery, excessive secretions, agitation, and untreated pneumothorax. 7 Although recent esophageal surgery is considered as a contraindication for NIV by some of the authors 7 , there are studies reporting the successful and safety use of NIV in the immediate early postoperative periods of laparoscopic Nissen fundoplication, Roux-en-Y gastric bypass, and even oesophagectomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that, careful patient selection and taking into account the risk factors and contraindications are important for NIV to be successful and safe. 1 Contraindications for NIV include respiratory or cardiac arrest, hypotension or shock, poor airway protective reflexes, recent upper airway surgery, excessive secretions, agitation, and untreated pneumothorax. 7 Although recent esophageal surgery is considered as a contraindication for NIV by some of the authors 7 , there are studies reporting the successful and safety use of NIV in the immediate early postoperative periods of laparoscopic Nissen fundoplication, Roux-en-Y gastric bypass, and even oesophagectomy.…”
Section: Resultsmentioning
confidence: 99%
“…These complications ranges from patient discomfort to life-threatening conditions like aspiration pneumonia or hypotension. 1 Herein, we describe a patient who developed early gastrostomy dislodgement, leakage to the abdominal wall, and subcutaneous emphysema related with NIV support after laparoscopic gastrostomy (LAPG) and Nissen fundoplication.…”
Section: Introductionmentioning
confidence: 99%
“…A common complication of NIMV is facial pressure ulcers (PU), which affects up to 50% 5,6 . In normal clinical practice, masks used in NIMV are tightly fitted to the face of the patient to achieve a tight seal, which is capable of reducing leakage and thereby ensuring the delivery of pressures, fraction of inspired oxygen (FiO 2 ) and programmed trigger sensitivity and cycling.…”
Section: Face Protective Patches Do Not Reduce Facial Pressure Ulcersmentioning
confidence: 99%
“…When a mask is chosen in consideration of the patient's personal features and is fixed appropriately, air leakages are reduced to an almost non-existent level. Taping the mask tightly can increase ventilation by preventing air leakages; however, it must be considered that taping too tightly can cause skin injuries (2). Injuries occurring in the nasal root are among the most frequently observed skin complications (24)(25)(26).…”
Section: 2mentioning
confidence: 99%
“…When compared with invasive mechanical ventilation (IMV), NIMV decreases the duration of stay in the hospital and intensive care unit, morbidity, and mortality in patients with acute and chronic respiratory failure (2). All patients with acute or chronic respiratory failure who do not show contraindications are NIMV candidates, provided that the necessary equipment and a trained team are available (3).…”
Section: Introductionmentioning
confidence: 99%